Dealing With Uncertainty: Testing Risk- and Ambiguity-Attitude Across Adolescence. Issue 1 (17th February 2016) - Blankenstein, Neeltje E.; Crone, Eveline A.; van den Bos, Wouter; van Duijvenvoorde, Anna C. K.
ABSTRACT: Attitudes to risk (known probabilities) and attitudes to ambiguity (unknown probabilities) are separate constructs that influence decision making, but their development across adolescence remains elusive. We administered a choice task to a wide adolescent age-range ( N  = 157, 10–25 years) to disentangle risk- and ambiguity-attitudes using a model-based approach. Additionally, this task was played in a social context, presenting choices from a high risk-taking peer. We observed age-related changes in ambiguity-attitude, but not risk-attitude. Also, ambiguity-aversion was negatively related to real-life risk taking. Finally, the social context influenced only risk-attitudes. These results highlight the importance of disentangling risk- and ambiguity-attitudes in adolescent risk taking.